Memórias familiares: um estudo da imigração italiana na quarta colônia imperial (Rio Grande do Sul, Brasil) - Stefanello, Liriana Zanon (Universidade do Vale do Rio dos Sinos, 2015)
The thesis is a study on the construction of family memories of immigrants in the region of the Fourth Imperial Colony of Italian Immigration of Rio Grande do Sul - Brazil. It addresses the trajectory of Pippi and Pigatto families, from Italy to Brazil seeking to analyze the mechanisms and dynamics used for insertion in the south of Rio Grande society and how they have maintained their memories. For that we study not only the strategies used by these immigrants to integrate into the host society but also how the memory itself and on itself was and is being built by and for their descendants. The development of memory is a social construct, therefore selecting what should be remembered and what is relegated to oblivion is part of any construction process of memory and identity. And more than that, understanding the individual as a social actor responsible for its history, family documents become heritage of a community when they represent it, because they carry the symbolic burden of representing in the present the past of each family. For these two families as well as hundreds of others, the construction of a memory - we call official - occurred through the creation of the Center for genealogy Research (CPG) of Nova Palma organized by Father Luiz Sponchiado (01/06/1984) in order to preserve the memory of this immigrant group. However one of the studied families has also reworked their memories in a particular way. The Pippi family, on building another memory itself, has created a private collection that has given to read another story / family memory, which ultimately tensed the official memory organized at the CPG. Nonetheless Pigatto family documents stored in CPG represent and are accepted as its memory at the Fourth Colony of Italian Immigration of the Rio Grande do Sul. In addition to this memorial character all documents are part of the cultural heritage of this community which want them stored in the CPG's collection, either in the private collection of Mrs. Maria Neli Donatto Pippi or unidentified others. Together they are part of this individuals search for identification and affirmation of a family memory. Each "chosen" document becomes then a symbol of remembrance that aims to reconstruct the trajectory, history and family memory.
Keywords: Memórias familiares; Família Pippi; Família Pigatto; Imigração italiana; Quarta colônia; Family memories; Pippi family; Pigatto family; Italian immigration; Fourth colony; ACCNPQ::Ciências Humanas::História